(untitled) (Bangladesh Journal of Medical Science, 2016)
Background: Hysterectomy is by far most common gynecological procedure. It is performed in our country for more or less similar indication as those performed in advanced countries. Sometimes clinical diagnosis does not correlate with histopathological findings. Objective: To find out the common indication of hysterectomy in tertiary level hospital; to detect the patterns of clinical presentation and to find out the correlation between pre and per operative findings with histopathology reports of specimen. Method: This is a cross sectional type of comparative study which was carried out on 150 cases from January 2013 to October 2013 in inpatient department of CMH Dhaka. Cases were randomly selected who were admitted for operative treatment. Result: The incidence of total abdominal hysterectomy was 73.33% and vaginal hysterectomy 26.67%. Highest incidence observed among the age group 35-40 year which was 46.66% in the study. The commonest indication of abdominal hysterectomy was Leiomyoma uterus 42.73% and most common symptom was Menorrhagia which was about 44.67% in the study. Leiomyoma uterus histopathologically correlated about 91.49% with clinical diagnosis. During examination it was found that least correlated diagnosis were DUB and PID respectively 70.83% and 73.33%. Ovarian tumor, CIN and chronic cervicitis correlated 100%. In this study, clinical diagnosis, pre-operative finding was similar with histopathology finding in 86.36%. Conclusion: The indication of hysterectomy in any case must be clearly defined and should be done for which conservative treatment is not likely to be efficacious. But advent of conservative treatment like ablation, Mirena IUS are as effective as hysterectomy which can offer the young age group of 35-40 year. Bangladesh Journal of Medical Science Vol.15(3) 2016 p.352-356